Targeted Therapy (TT) Use in Patients With Cancer ≥ 85 Years of Age. (11th November 2018) - Wickersham, K; Weiss, M; Crothers, M; Puth, D; Powell, K; Resnick, B
Abstract: Significance: TTs are approved by use for patients with cancer by demonstrating efficacy in prolonging survival, improving quality of life, or both. However, little is known about older adults who take TT for cancer, including factors that influence whether or not they receive these medications. Objective: Describe sociodemographic and clinical profiles of patients aged ≥85 years who receive TTs. Specifically, we hypothesized that worse performance status and female gender would be associated with taking multiple TTs for cancer. Methods: This was a secondary analysis of a study that retrospectively examined electronic medical records for patients ≥85 years taking TT. Sociodemographic information and clinical information, performance status, and TT use were collected. Descriptive statistics were computed to describe the data distributions and to characterize the study sample. We used the χ2 test of independence to compare patients who received one TT for one cancer versus those who received multiple TTs for once on select study variables. Results: The mean age of the participants was 85 and more than half (55.6%) were female. When comparing patients who took one TT (n = 200) with those who took multiple TTs (n = 95), we found significant differences in gender (p = .027), marital status (p = .042), performance status (p = .017), and tumor mutational testing (p = .003). Conclusions: We found sociodemographic and clinical differences between the two groups of patients in our sample, suggesting that further exploration of potential predictors of TT use and persistence is needed in patients ≥85 years.